Animal Models of Thrombosis From Zebrafish to Nonhuman Primates: Use in the Elucidation of New Pathologic Pathways and the Development of Antithrombotic Drugs. Issue 9 (29th April 2016) - Jagadeeswaran, Pudur; Cooley, Brian C.; Gross, Peter L.; Mackman, Nigel
Abstract : Thrombosis is a leading cause of morbidity and mortality worldwide. Animal models are used to understand the pathological pathways involved in thrombosis and to test the efficacy and safety of new antithrombotic drugs. In this review, we will first describe the central role a variety of animal models of thrombosis and hemostasis has played in the development of new antiplatelet and anticoagulant drugs. These include the widely used P2Y12 antagonists and the recently developed orally available anticoagulants that directly target factor Xa or thrombin. Next, we will describe the new players, such as polyphosphate, neutrophil extracellular traps, and microparticles, which have been shown to contribute to thrombosis in mouse models, particularly venous thrombosis models. Other mouse studies have demonstrated roles for the factor XIIa and factor XIa in thrombosis. This has spurred the development of strategies to reduce their levels or activities as a new approach for preventing thrombosis. Finally, we will discuss the emergence of zebrafish as a model to study thrombosis and its potential use in the discovery of novel factors involved in thrombosis and hemostasis. Animal models of thrombosis from zebrafish to nonhuman primates are vital in identifying pathological pathways of thrombosis that can be safely targeted with a minimal effect on hemostasis. Future studies should focus on understanding the different triggers of thrombosis and the best drugs to prevent each type of thrombotic event.